A discourse analysis of prefaces in english and vietnamese books on linguistics - Đỗ,Thùy Dương (ĐHNN, 2016)
This study aims at conducting a discourse analysis of the prefaces of English and Vietnamese books on linguistics. The data for analysis in this thesis are 80 samples of the prefaces of English and Vietnamese books on linguistics (40 in English and 40 in Vietnamese) collected well-known books. The study is carried out based on the theories of discourse analysis and a combination of a variety of methods such as descriptive, comparative, contrastive, analytic and inductive. The study focuses on analyzing some typical discourse features in order to point out the similarities and differences between English linguistic book prefaces and Vietnamese linguistic book prefaces in terms of their layout, semantic features, syntactic features and cohesive devices. The findings of this study are clearly presented based on 40 English linguistic book prefaces (ELBPs) and 40 Vietnamese linguistic book prefaces (VLBPs). Hopefully, the results of the study will really provide some practical applications for teaching and learning English. This study may also be useful for those who are interested in writing prefaces of books.
Keywords: discourse analysis; prefaces in english; vietnamese books; linguistics